The Effect of Air Flow on a Building Integrated PV-panel - Kalogirou, Soteris A.; Aresti, Lazaros; Christodoulides, Paul; Florides, Georgios A. (My University, 2014)
Photovoltaic (PV) materials are increasingly being incorporated into the construction of new buildings for generating electrical power and are used to replace conventional building materials in parts of the building envelope such as the roof, skylights, or facades. Also photovoltaic systems may be retro it - integrated into existing buildings. The advantage of integrated photovoltaic systems over the non-integrated systems is that their initial cost can be offset by reducing the cost of the materials and labo r that would normally be spent to construct the part of the building that is replaced. This study examines the effect of air flow on a building integrated PV-panel. It is shown that in summer, the maximum temperature of a PV-panel of 3 m in height is experienced for an east facing surface and reaches 77 °C early in the mornin. The maximum temperature for a south facing panel is 51 °C and that for a west fac ng surface is 58 °C. The air velocity in the air-gap between the PV-panel and the building wall is an important factor. It is shown that for an air-gap width of 0.02 m, an air velocity of 0.5 m s–1 can lower the mean temperature of the panel from 77 °C to 39 °C, allowing for a significant increase in its efficiency. Finally the air-gap width is varied for a steady elocity of 0.2 m s–1, and it is shown that the temperature of the building wall varies from 23.7 °C for a width of 0.01 m to 20 °C for a width of 0.05 m.
Keywords: Photovoltaics; Building integration; Convection heat transfer; Thermal modeling